Angiosarcoma With Malignant Peripheral Nerve Sheath Tumour Developing in a Patient With Klippel–Trénaunay–Weber Syndrome. (2005) - Ploegmakers, Marieke J. M.; Pruszczynski, Maciej; De Rooy, Jacky; Kusters, Benno; Veth, René P. H.
Abstract : Purpose: We discuss the coexistence of Klippel–Trénaunay–Weber syndrome with various malignancies, the possible histogenetic pathways and therapeutic implications. Patient: We report on a 46-year-old man presenting with increasing pain and swelling of his right lower leg after fracturing his fibula. Since birth he was known as having the uncommon syndrome of Klippel–Trénaunay–Weber of his right lower leg. Methods: Our patient underwent an above-knee amputation for biopsy-proven malignant vascular tumour, first thought to be a composite hemangio-endothelioma and/or angiosarcoma with lung metastases. Results: In the amputated extremity, a vascular malformation was found with tumour showing various components with foci of angiosarcoma adjacent to diffuse neurofibroma and areas with high-grade malignant peripheral nerve sheath tumour. Amputation and palliative chemotherapy were indicated, but he died of pulmonary and cerebral metastases 2 months postoperatively. Discussion: This case describes an angiosarcoma with malignant peripheral nerve sheath tumour developing in a patient with Klippel–Trénaunay–Weber syndrome. A case never described before in literature and probably, as in our case, difficult to diagnose at first biopsy.